Reference genes identification for qRT-PCR normalization of gene expression analysis in Cucumis sativus under Meloidogyne incognita infection and Pseudomonas treatment - Ji, Tingting; Ma, Si; Liang, Meiting; Wang, Xueyun; Gao, Lihong; Tian, Yongqiang (Frontiers in Plant Science, 2022)
qRT-PCR is a common and key technical means to study gene expression in biological research. However, reliability and accuracy of quantification by qRT-PCR is entirely dependent on the identification of appropriate reference genes. Cucumber as an economical vegetable is widely cultivated worldwide and is subject to serious nematode infection, especially from M. incognita. Plant could employ beneficial soil bacteria in the rhizosphere to enhance plant adaptability to various stresses. In this study, the optimal reference genes in cucumber under M. incognita stress and Pseudomonas treatment were calculated and confirmed. A total of thirteen candidate reference genes were identified across three different treatments. Of these, geNorm, NormFinder and BestKeeper programs combined RefFinder software identified EF1 and UBI are the most suitable reference gene in the root knot and whole root of cucumber infected M. incognita, respectively, and CACS is the most suitable reference gene in the whole root of cucumber treated by Pseudomonas. The work first validated the most suitable reference genes for the normalization gene expression in cucumber by nematode infected or Pseudomonas inoculated, and these results would facilitate the further research on M. incognita or Pseudomonas soil rhizosphere microbe interaction with cucumber.